Эндодонтические аспекты сравнительной морфометрии моляров (Эндодонтия Today)
For the first time on 84 removed molars of both jaws some morphometric parameters such as thickness of firm tissues of chewing surface (ТFT), safe depth of pulpar chambers disclosing (SDD), bottom thickness of a tooth cavity (BТТ ) are investigated. It is shoun that the depth of the top molars crown cavity is bigger. Together with the bigger BТТ that can explain lesser risk and lesser frequency of occurrence furcation perforations of there teeth. Practicing doctors knowledge of the described parameters of endodontic safety will help to prevent the line of serious complications of endodontic treatment.